Pengaruh Fasilitas Dan Word Of Mouth Terhadap Keputusan Pembelian Pada Perumahan Sejahtera Indah 2 Kota Medan - Nababan, Octavia Mia; Tarigan, Eka Dewi Setia (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2025)
This study examines the influence of facilities and word of mouth on purchasing decisions in the Sejahtera Indah 2 housing complex in Medan City, which consists of 112 building units. Using a sample of 95 respondents. This study aims to understand consumer needs related to housing and effective promotional strategies in driving purchasing decisions. The main focus of the study is to explore how visual and interactive promotional media can influence consumer behavior in the context of property sales. A quantitative approach with an associative design is used to examine the relationship between the independent variables, namely facilities and word of mouth, on the dependent variable, namely purchasing decisions. Data were collected through questionnaires, interviews, and literature studies and analyzed using multiple linear regression to obtain valid empirical results. The findings of this study are expected to provide strategic insights for housing developers in increasing product appeal and promotional effectiveness to significantly increase consumer purchasing decisions.